2010
DOI: 10.1111/j.1440-1746.2010.06502.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of hepatocellular adenoma in China and other regions

Abstract: Hepatocellular adenoma (HCA) is a benign liver neoplasm with a risk of spontaneous bleeding and malignant transformation. The aim of this review article is to review all the case reports and case series of patients with HCA from 1998 to 2008 in China and other parts of the world in order to compare clinical presentation, surgical management and outcomes. A search for all reports of HCA in the world literature from 1998 to 2008 was performed. A total of 356 patients were identified, including 191 patients from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 23 publications
2
66
1
Order By: Relevance
“…There is no conclusive evidence to prove a correlation of the size of HA and rupture; some authors report an increased risk of rupture in tumors more than 6.5 cm in size [ 17 ]. A report, analyzing the evolution of HAs and their risk of rupture, found that the mean diameter of the lesions in China, Europe, and North America were 10.8, 12.4, and 14 cm, respectively [ 5 ]. There are two types of hemorrhage which are mostly observed in HA: hemorrhage inside the HA nodule, usually admixed with necrotic changes, and spontaneous hemorrhagic rupture which can cause subcapsular hematoma and possible hemoperitoneum.…”
Section: Evolutionmentioning
confidence: 93%
See 3 more Smart Citations
“…There is no conclusive evidence to prove a correlation of the size of HA and rupture; some authors report an increased risk of rupture in tumors more than 6.5 cm in size [ 17 ]. A report, analyzing the evolution of HAs and their risk of rupture, found that the mean diameter of the lesions in China, Europe, and North America were 10.8, 12.4, and 14 cm, respectively [ 5 ]. There are two types of hemorrhage which are mostly observed in HA: hemorrhage inside the HA nodule, usually admixed with necrotic changes, and spontaneous hemorrhagic rupture which can cause subcapsular hematoma and possible hemoperitoneum.…”
Section: Evolutionmentioning
confidence: 93%
“…The issue of when HA develops into malignancy and which factors infl uence malignant degeneration are still being investigated. In some reports [ 5 ] a total of 5.6 % showed HCC foci within an adenoma upon fi nal pathology; the mean size of the tumor with HCC was larger than the mean tumor diameter in benign HA (11.2 cm vs 7.8 cm). The risk of malignancy is particularly higher for β-catenin mutation HA, which are most frequently associated with glycogenosis type I, androgenic hormone intake, and familial adenomatous polyposis.…”
Section: Evolutionmentioning
confidence: 93%
See 2 more Smart Citations
“…Hepatocellular carcinoma (HCC) is one of the most frequent causes of death from solid tumors in the world, particularly in China (1,2). Currently, surgical intervention, including hepatic resection and liver transplantation, is the only therapy considered to provide a cure.…”
Section: Introductionmentioning
confidence: 99%